MENINGKATKAN LOYALITAS PEGAWAI KOPI NAU DI KABUPATEN BULELENG MELALUI KEPEMIMPINAN, KOMPENSASI FINASIAL DAN MASA KERJA - DEWI, KOMANG TRISNA SARI; SUARDIKA, I KETUT; PURWANTARA, I KOMANG GDE TRISNA; SARI, GUSTI AYU DIAH KUSUMA (Universitas Mahasaraswati K. Mataram, 2024)
The importance of HR regulation occurs because the human element is the main actor in every operational activity of a company. Therefore HR is the main requirement to be able to carry out all activities in various organizational fields within the company. However, a number of problems were found related to leadership style, financial funding, tenure and loyalty to employees, especially employees of PT Kopi Nau Indonesia so that the examiners were interested in researching the role of